2016
DOI: 10.1002/ceat.201500101
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Replaceable Microreactor Coated with a CuZnFe Nanocatalyst for Methanol Steam Reforming

Abstract: A methanol steam microreactor with a replaceable catalytically coated plate structure was designed. A splitting‐jointing flow (SJF) design was proposed to increase the efficiency. Stainless‐steel plates were coated with a Cu/Zn/Fe nanocatalyst. Electrophoretic deposition served as a uniform and controllable coating technique to evaluate the performance of the nanocatalyst and the microchannel design. The functioning of the SJF design for methanol conversion was found to be only slightly dependent on the plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The activity tests of the catalyst coatings were conducted in a stainless‐steel plate microreactor 37 in the medium temperature range of 300–390 °C. The stainless‐steel microreactor has splitting‐joining channels (108 mm × 1 mm × 30 μm) for passing of the feed flow 38.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity tests of the catalyst coatings were conducted in a stainless‐steel plate microreactor 37 in the medium temperature range of 300–390 °C. The stainless‐steel microreactor has splitting‐joining channels (108 mm × 1 mm × 30 μm) for passing of the feed flow 38.…”
Section: Methodsmentioning
confidence: 99%
“…The SUS 304 plates were operated as electrodes that were connected to two anodes and a cathode, separated by a distance of 1.5 cm. EPD of the catalyst powder on the cathode was carried out at a constant voltage of 140 V, applied by using a direct current (DC) power supply (SPS-900NP; Navasanpardaz) for 3 min to achieve the desired deposition (the optimal conditions of voltage and time are described in previous work [37]). Following the primary drying at room temperature, the deposit was carefully taken out of the setup.…”
Section: Suspension Preparation and Coating Proceduresmentioning
confidence: 99%
“…While a supply of hydrogen is needed to effectively use such technology, hydrogen is extremely hard to store and transport [2]. The reformation of liquid fuels offers a reliable solution for the generation of hydrogen [3,4]. Methanol is one of the most favorable liquid fuels for the production of hydrogen due to its low cost, boiling point, and reforming temperature [5].…”
Section: Introductionmentioning
confidence: 99%
“…As they stated, when a thin-film layer of the catalysts was formed on the plate, carbon deposition was remarkably lower. In Irankhah et al's study, 11 methanol steam reforming was investigated and the performance of a microreactor was compared to that of a fixed-bed reactor. The findings of the mentioned study showed that, although a higher amount of methanol was converted in the fixed-bed reactor, hydrogen yield was better in the microreactor.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the performance of microchannel reactors is superior to that of fixed-bed reactors. , For instance, it has been shown that due to the rapid transfer of mass and heat in the microchannel reactor, its activity and hydrogen selectivity are better than those of fixed-bed reactors . In a study that aimed at comparing the efficiencies of a microreactor and a conventional fixed-bed reactor in partial oxidation of dimethyl ether, it was found that in the presence of enough catalyst (0.5 wt % Rh), the two studied reactors had a high hydrogen yield (>90%); however, when Rh content was decreased, the reaction efficiency of fixed-bed reactor decreased and the microreactor did not change.…”
Section: Introductionmentioning
confidence: 99%